A Translation Analysis Of Past Sentences Found In Novel Twilight And Its Translation - Saputro, Dedik, Dr. Dwi Harjanti, M.Hum (2016)
This research aims to identify the type of translation stratgies and to describe the accuracy of the Indonesian translation found in novel Twilight. The type of this research is descriptive qualitative. The object of this research is the past sentences found in novel Twilight. The data are all sentences belong to past sentence in the novel and the translation. The writer uses the documentation as method to collect the data. Then to prove the validity of the data, the writer uses triangulation. The data sources are the novel and informant. The results of the research show that first, 8 data or 5,07% of past sentences as adaptation; 15 or 9,50% data belongs to particularization; 23 data or 14,55% as transposition; the addition has 83 data or 52,53%; and compensation has 29 data or 18,35%. Second, the data that belong to past senences in novel Twilight, there are 153 data or 96,83% data that belong to accurate translation, then 4 data or 2,54% that is categorized as less accuracy, and only 1 data or 0,63% data is included not accuracy translation.